Seismic damage evaluation of reinforced concrete slit walls. Issue 2 (20th April 2015) - Baetu, Sergiu Andrei; Barbat, A H; Ciongradi, Ioan Petru
Abstract : Purpose: – The purpose of this paper is to investigate a dissipative reinforced concrete structural wall that can improve the behavior of a tall multi-storey building. The main objective is to evaluate the damage of a dissipative wall in comparison with that of a solid wall. Design/methodology/approach: – In this paper, a comparative nonlinear dynamic analysis between a dissipative wall and a solid wall is performed by means of SAP2000 software and using a layer model. The solution to increase the seismic performance of a reinforced concrete structural wall is to create a slit zone with short connections. The short connections are introduced as a link element with multi-linear pivot hysteretic plasticity behavior. The behavior of these short connections is modeled using the finite element software ANSYS 12. In this study, the authors propose to evaluate the damage of reinforced concrete slit walls with short connections using seismic analysis. Findings: – Using the computational model created in the second section of the paper, a seismic analysis of a dissipative wall from a multi-storey building was done in the third section. From the results obtained, the advantages of the proposed model are observed. Originality/value: – A simple computational model was created that consume low processing resources and reduces processing time for a dynamic pushover analysis. Unlike other studies on slit walls with short connections, which are focussed mostly on the nonlinear dynamic behavior of the short connections, in this paper the authors take into consideration the whole structural system, wall and connections.